Traumatic Experiences in Colum McCann’s "Apeirogon" - Stephanus Rexy Irawan (Morphosis: Journal of Literature, 2024)
This study analyzed the trauma of the two main characters caused by traumatic experiences in the novel Apeirogon by Colum McCann. It explained how the trauma is portrayed in which it is explained as traumatized responses that the two main characters experienced. It used psychoanalytic perspectives of trauma from Cathy Caruth and qualitative approach to create the analysis. The theory was used to classify the responses of trauma that the two main characters showed. The responses of trauma analyzed are disruption, avoidance, and hyper-arousal. The responses were classified based on how the two main characters respond the trauma including having negative and intrusive thoughts, flashbacks and dreams, avoiding things, places and people, and having negative feelings. The data were collected by highlighting the relevant events that were narrated in the novel. The study also aimed to find out how the two main characters deal with the trauma that affects their daily life. The result has found out that the two main characters have shown the three responses of trauma in the novel and it also has found out the connection of traumatized people in which it leads the two main characters to use the force of their grief to deal with the trauma. Keywords: avoidance, disruption, fictional devices, hyper-arousal, traumatic experience